Comparison of ratoon yield under high-level cutting in two varieties of forage sugarcane, KRFo93-1, and Shimanoushie. (3rd April 2017) - Sakaigaichi, Takeo; Terajima, Yoshifumi; Terauchi, Takayoshi
Abstract: High-level cutting without stubble shaving has been recommended in the cultivation of forage sugarcane, KRFo93-1. However, it is unclear whether this management practice is appropriate for the more recently developed variety Shimanoushie. Therefore, the aim of this study was to compare the dry matter yield of both varieties to high-level cutting. The study included five ratoon crops (RC1–RC5). In KRFo93-1, dry matter yield was higher in HC plots (high-level cutting without stubble shaving plots) than in Control plots (stubble shaving after high-level cutting plots), and the differences were significant for the first three ratoon crops. A similar trend was observed in Shimanoushie; however, the dry matter yield of HC plots was slightly lower than Control plots in RC4 and RC5 owing to a lower stem number. Although the sum of dry matter yield of five ratoon crops was significantly higher in HC plots of both varieties, the influence of high-level cutting was more effective in KRFo93-1 than in Shimanoushie.